Evaluating Pedagogical Training Needs of Science Teachers for Effective Teaching: A Rural-Urban Comparison (Journal of Asian Development Studies, 2025)
The study was designed to identify the pedagogical training needs (PTNs) of science teachers (STs) for effective teaching (ET) and to compare the differences in their PTNs between rural and urban settings. This study employed a descriptive design and utilized a survey method. The study included students from public secondary schools in Rahim Yar Khan district. Three hundred and twenty (320) STs were selected using a multi-stage random sampling process. Data was collected using a 5-point Likert scale. The data were analyzed with mean, SD, and t-tests. The study found that most respondents require pedagogical training for ET, and there are considerable differences in perceptions between rural and urban STs.